Construction delays: a case study in the Brazilian Amazon - Maués, Luiz Mauricio Furtado; Santana, Wylliam Bessa; Santos, Paulo Cerqueira dos; Neves, Renato Martins das; Duarte, André Augusto Azevedo Montenegro (Ambiente Construído, 2017)
The construction industry is one of the industrial sectors with the lowest rates of fulfilment of contract deadlines, especially in developing countries. This fact has been the focus of considerable discussions seeking to identify the causes of the delays. The main purpose of this paper is to use factor analysis to identify the factors that are correlated with delay, contemplating exclusively residential real estate projects and using a city in the Brazilian Amazon as a case study. Based on the database from the government agency that authorises constructions in the city of Belém (City Planning Department – Secretaria Municipal de Urbanismo, SEURB) and data from construction companies, the study investigated 274 construction projects from the past 11 years. Factor analysis and work with the variables that can be identified and measured in the initial phase of the project, i.e., during the feasibility study, demonstrate that the physical characteristics of the apartments and the construction project are the primary causes for variations in construction delays; these causes have not yet been reported in the literature. We hope that the results of this study will contribute to more consistent forecasting of construction time, minimising the risk of delays.